Otonomi Daerah Dalam Perspektif Pancasila - Taufiq Yuli Purnama; Mudji Rahardjo; Sigit Sapto Nugroho; Heru Kuswanto (Universitas Merdeka Madiun, 2022)
Abstract- In Indonesia, the state has a state basis, namely Pancasila, Pancasila is also a source of law and basic norms for organizing government administration. Pancasila can also be interpreted as the ideals of the Indonesian nation. In realizing regional autonomy in the government administration system, basic norms are needed to achieve it. There is a need for harmony between Law Number 23 of 2014 concerning Regional Government and the 1945 Constitution as mandated by Pancasila. In Indonesia, the highest power holder is the central government, but the location of the Indonesian state is very wide and consists of large and small regions so that in carrying out its authority, the central government is obliged to provide the competent authority. The method used in this journal is normative juridical. To manage their respective regions is called decentralization or regional autonomy. The principle of the Unitary State of the Republic of Indonesia cannot be separated from the principle of Regional Autonomy Article 18 of the 1945 Constitution, therefore Regional Autonomy is a subsystem of the power system of the Unitary State of the Republic of Indonesia. then in aggregate it will contribute to national welfare. Meanwhile, one dimension of the decentralization policy is improving the quality of public services. The estuary of these characteristics is realizing the constitutional mandate, namely realizing general welfare and educating the nation's life.